Method for detecting rough road index using iot sensor fusion and v2v interaction for efficient road infrastructure management - Akhilesh Kumar Singh; Damodar Reddy Edla (MethodsX)
The method proposed explores the integration of Internet of Things (IoT) technologies and sensor fusion techniques into modern transportation systems to enhance efficiency, safety, and road quality assessment. The study not only emphasizes the importance of V2V communication using DSRC Dedicated Short Range Communication, Threshold Based Algorithms (TBA) and Dynamic Time Warping (DTW) but also proposes a novel approach of IoT multi-sensor fusion hardware model that is designed to identify clean and rough surface road conditions. By deploying multi sensor module into proposed model, real-time road surface data is collected and processed to classify them into flat clean or bumpy rough categories based on their smoothness index. In order to monitor the road surface in real time, this study suggests a novel IoT-based multi-sensor fusion hardware architecture that combines LiDAR, accelerometer, and ultrasonic sensors. • To improve road safety and navigation, the suggested methodical system makes advantage of DSRC-enabled V2V communication, primarily for luxury and driverless cars. • The proposed method provides revolutionary possibilities for intelligent transportation systems and fills in gaps in the high-accuracy identification of road anomalies.